Direct Electrochemical Addressing of Immobilized Alcohol Dehydrogenase for the Heterogeneous Bioelectrocatalytic Reduction of Butyraldehyde to Butanol. Issue 6 (20th February 2015) - Schlager, S.; Neugebauer, H.; Haberbauer, M.; Hinterberger, G.; Sariciftci, N. S.
Abstract Modified electrodes using immobilized alcohol dehydrogenase enzymes for the efficient electroreduction of butyraldehyde to butanol are presented as an important step for the utilization of CO2‐reduction products. Alcohol dehydrogenase was immobilized, embedded in an alginate–silicate hybrid gel, on a carbon felt (CF) electrode. The application of this enzyme to the reduction of an aldehyde to an alcohol with the aid of the coenzyme nicotinamide adenine dinucleotide (NADH), in analogy to the final step in the natural reduction cascade of CO2 to alcohol, has been already reported. However, the use of such enzymatic reductions is limited because of the necessity of providing expensive NADH as a sacrificial electron and proton donor. Immobilization of such dehydrogenase enzymes on electrodes and direct pumping of electrons into the biocatalysts offers an easy and efficient way for the biochemical recycling of CO2 to valuable chemicals or alternative synthetic fuels. We report the direct electrochemical addressing of immobilized alcohol dehydrogenase for the reduction of butyraldehyde to butanol without consumption of NADH. The selective reduction of butyraldehyde to butanol occurs at room temperature, ambient pressure and neutral pH. Production of butanol was detected by using liquid‐injection gas chromatography and was estimated to occur with Faradaic efficiencies of around 40 %.